NITROGEN MINERALIZATION RATE IN COMBINED APPLICATION OF ORGANIC AND INORGANIC NITROGEN FERTILIZERS ON INCEPTISOL’S BENGKULU - Kartika Utami; Hepyliani Marsanda; Sukisno; M. Faiz Barchia; H. Gusmara (Gunung Djati Conference Series, 2026)
Inceptisol is characterized by poor soil chemical properties, particularly a deficiency of nitrogen (N), one of the essential macronutrients required by plants in large amounts but typically present in soil at low availability. This study aimed to determine the rate of N mineralization resulting from the combined application of ZA fertilizer (21% N) and cow manure on Inceptisol soil from Bengkulu. The experiment was conducted from November 2023 to March 2024 at the Soil Science Laboratory, Faculty of Agriculture, University of Bengkulu, using a single-factor Completely Randomized Design (CRD) with four treatments: 100% ZA fertilizer (400 kg ha⁻¹), 50% ZA + 50% organic fertilizer, 30% ZA + 70% organic fertilizer, and 100% organic fertilizer (25,000 kg cow manure ha⁻¹), each replicated three times across five incubation intervals (7, 14, 28, 42, and 70 days after incubation/DAI), producing 60 experimental units. Ammonium (NH4⁺) and nitrate (NO3⁻) concentrations were measured periodically, and the mineralization rate was calculated using a first-order kinetic model. The results showed that the combination of 50% ZA and 50% organic fertilizer produced the highest NO3⁻ mineralization rate (2.37 ppm day⁻¹), while 100% organic fertilizer produced the highest NH4⁺ mineralization rate (0.93 ppm day⁻¹). Sole application of ZA fertilizer resulted in a negative NH4⁺ mineralization rate (-2.96 ppm day⁻¹), indicating rapid conversion of NH4⁺ into NO3⁻ through nitrification. These findings suggest that the combination of inorganic and organic N fertilizers provides a more sustained and balanced N mineralization pattern than either fertilizer applied alone, offering a practical strategy for improving N availability in Inceptisol soils.